Physicochemical Characteristics and In Vitro Starch Digestibility of Spontaneously Combined Submerged and Solid State Fermented Cassava (Manihot esculenta Crantz) Flour - Indrastuti, Erning; Estiasih, Teti; Zubaidah, Elok; Harijono (Current Nutrition & Food Science, 2019)
Background: High cyanide varieties of cassava must be detoxified before consumption. Several studies showed detoxification of cassava by slicing, submerged fermentation (soaking), solid state fermentation, and drying. One of traditional detoxification is combination of submerged and solid state fermentation and the effect of this processing on cyanide reduction and food properties has not been evaluation yet. Objective: This research studied the effect of solid state fermentation time on physicochemical, starch granule morphology, and in vitro starch digestibility of cassava flour from high cyanide varieties of Malang 4, Malang 6, and Sembung. Methods: Three varieties of high cyanide grated cassavas were soaked for 3 days in ratio of water to cassava 1:1. After draining for 1 hour, grated cassava was placed in a bamboo container and put in a humid place for 3-day solid state fermentation. Fermented grated cassavas were then dried, milled, and analyzed. Results: Solid state fermentation similarly affected cyanide reduction and characteristics of cassava flour for three high cyanide varieties. The detoxification process reduced cyanide to 89.70-93.42% and produced flour with a total cyanide of 8.25-10.89 mg HCN eq/kg dry matters, which is safe to consume. Fermentation decreased cyanide, starch content, titratable acidity, swelling power, and solubility; meanwhile pH, amylose content, water absorption, oil absorption, and in vitro starch digestibility increased in all three varieties studied. Submerged fermentation reduced the pH thus inhibiting the degradation of linamarin and cyanohydrin into free HCN. pH value was increased by solid state fermentation, from 4.43 to 6.90 that optimum for linamarin and cyanohydrin degradation into free HCN. The submerged and solid-state fermentation indeuce spontaneous microbial growth that affected chemical composition of cassava flour. The changes of structure and morphology of starch granules affected pasting properties, and Increased in vitro starch digestibility due to damaged granules. Conclusion: Solid-state fermentation reduced cyanide content of all three cassava varieties into the safe level for consumption, and aiso changed chemical, physical, and functional characteristics and starch digestibility of cassava flour.
Keywords: free HCN